Inclusion items and financial risk assessment in systems with grazing sheep under the concentrated supplementation - Chambela Neto, Alberto; Ramalho Haddade, Ismail; Alfonsa Vieira Lo Monaco, Paola; Haddad Souza Vieira, Gustavo; Gomes da Silveira Deminicis, Renata; Deminicis, Bruno Borges (Scientia Agraria Paranaensis, 2021)
The aim of this study was to evaluate the sensitivity and financial risk in two production systems of beef sheep, in grazing, with and without the use of concentrate, in Santa Teresa County - Espírito Santo State, Brazil. A cash flow spreadsheet was prepared. Through the sensitivity analysis it was shown that greater attention should be directed to the sale of finished animals and their acquisition. These, in descending order of relevance, followed by labor, in the system with no concentrate, and concentrated supplementation, in the system where it was present. Then, the Monte Carlo simulation was performed. Probabilities of 37.9 and 33.3% that the systems without and with the concentrate, respectively, were financially unfeasible were observed. Considering the alternative remuneration of 6%, there is a considerable risk for both options, perhaps because the proposed scenarios consider the need to implement all the infrastructure for the activity, in addition to the reduced size of the production module. The strategic use of concentrated supplement as a complement to pasture presents itself as an alternative that can reduce financial risk and increase income in intensive systems of production of beef sheep in grazing. The labor efficiency is an item that affects the financial efficiency of beef sheep production systems on pasture, especially in situations of weight gain of animals without the use of concentrated supplementation. The reduction of financial risk with the use of concentrated supplementation. Intensive grazing sheep production systems can be financially advantageous and the strategic use of concentrate can result in increased income and reduced financial risk associated with this type of production.